2015
DOI: 10.9734/bjast/2015/17970
|View full text |Cite
|
Sign up to set email alerts
|

Obtained Yield and Financial Parameters of Organically Grown Mint in the Republic of Macedonia

Abstract: Aims: The objective of this paper is to present the soil and weather conditions, applied production technology and to demonstrate the economic viability of irrigated and organically grown Mint (Mentha piperita). Methodology: The obtained yield results are in reference to the open field growing conditions. In order to present the results in clear and understandable manner, standard methods for cost calculation were applied, usual for organic plant production. In order to obtain comparable results, the processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…For instance, Wilson et al (2011) have reported the initial cost of peppermint plantation establishment of $ 3360, but this calculation included stolone purchase, fixed costs, and insecticide application. On the other hand, Mihajlov et al (2015) calculated the profit of 1569 e and 8125 e for the first and second years of cultivation, respectively. From our experience, mint plants do not form an adequate habitus in the second year due to soil compaction and energy consumption for underground reproduction.…”
Section: Peppermintmentioning
confidence: 99%
“…For instance, Wilson et al (2011) have reported the initial cost of peppermint plantation establishment of $ 3360, but this calculation included stolone purchase, fixed costs, and insecticide application. On the other hand, Mihajlov et al (2015) calculated the profit of 1569 e and 8125 e for the first and second years of cultivation, respectively. From our experience, mint plants do not form an adequate habitus in the second year due to soil compaction and energy consumption for underground reproduction.…”
Section: Peppermintmentioning
confidence: 99%